Development of rapid screening method for low-yielding chitosanase activity using Remazol Brilliant Blue-chitosan as substrate - Fen, Lee Lih; Md.Illias, Rosli; Kamaruddin, Kamarulzaman; Maskat, Mohd Yusof; Hassan, Osman (Elsevier BV, 2006)
Chitosanolytic activity was monitored using chitosan impregnated with Remazol Brilliant Blue R dye (RBB). Low-yielding chitosan (1%, w/v) hydrolysis was modelled using Viscozyme® L (50%, w/w), a commercial mixed-glucanase, and was found to perform optimally at pH 4.5 and 50 °C. The chitosanase assay was performed on powdered (RBB-P) and colloidal form (RBB-C) of the dyed chitosan. Hydrolysis of chitosan was accompanied by the release of water-soluble dyed-hydrolysate, which can be monitored rapidly using microplate reader at 595 nm. The result obtained from this method was in agreement with the determination of reducing end by using the traditional, complex and time-consuming DNS method. The method is significantly rapid and more sensitive than DNS method.